A system dynamics model to support marine spatial planning in Algoa Bay, South Africa. (February 2023) - Vermeulen-Miltz, Estee; Clifford-Holmes, Jai Kumar; Scharler, Ursula M.; Lombard, Amanda T.
Abstract: The foundation of a healthy marine environment is central to the ecosystem-based management approach and is recommended for achieving sustainable development outcomes in marine spatial planning. Algoa Bay, South Africa, features a metropolitan area, protected natural area and hosts a range of uses that are closely interconnected with the health of the marine system. Future trajectories of marine uses and related marine sustainability goals are expected to develop according to shifting needs of various sectors operating in the bay. We therefore leverage the application of system dynamics modelling, to explore these trends and the underlying feedback effects between marine uses and the marine environment by developing the Algoa Marine Systems Analysis Tool. The model is used to investigate sustainability outcomes under alternative scenarios over time, and demonstrates how multiple, cross-sectoral management interventions can result in system-wide change and can be used to achieve desirable marine sustainability goals in the long-term. Graphical abstract: Image 1 Highlights: A system dynamics model explores the temporal change of marine activities to inform ecosystem-based marine spatial planning. Trade-offs between marine sustainability goals are explored in four scenarios. The model identifies leverage points for management or policy interventions. A model interface facilitates model use in a collaborative planning environment.